Electrocatalytic Oxidation of Amines on a Mediator‐Modified Electrode by Electrochemical Copolymerization of Nitroxyl Radical Precursor Containing Pyrrole Side Chain and Bithiophene. Issue 12 (15th November 2013) - Kashiwagi, Yoshitomo; Takamori, Yumiko; Yoshida, Kentaro; Ono, Tetsuya
Abstract This paper describes the electrocatalytic oxidation of amines on TEMPO (2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl)‐modified electrodes prepared by electrochemical copolymerization of TEMPO precursor containing pyrrole side chain and 2, 2′‐bithiophene. The modified electrode exhibits electrocatalytic activity for the oxidation of primary and secondary amines. Cyclic voltammetric studies showed that the peak current of the cyclic voltammogram increased linearly with increasing concentration of amine in the sample solution.